Influence of particle size of Enogen Feed corn and conventional yellow dent corn on lactating sow performance - Williams, Hadley R (Transl Anim Sci, 2021)
Enogen Feed corn is a variety developed by Syngenta Seeds (Downers Grove, IL) that has been genetically modified to contain an -amylase enzyme trait (SYT-EFC). Originally, Enogen feed corn was developed for the ethanol industry due to its properties for reducing the viscosity of its corn mash. There is potential application for Enogen Feed corn to be used in livestock diets due to the potential for the increase in - amylase enzyme to increase the starch digestibility. Because of this, it may be possible to increase the particle size of ground Enogen Feed corn and maintain the same starch digestibility as finely ground conventional yellow dent corn. Therefore, our hypothesis was that an interaction between corn source and particle size would exist such that the performance of sows fed fine ground conventional yellow dent corn would be similar to sows fed coarse ground Enogen Feed corn. A total of 107 sows (Line 241; DNA, Columbus, NE) across four batch farrowing groups were used to evaluate sow and litter performance. Treatments were arranged in a 2 2 factorial with main effects of corn source (Enogen Feed corn or conventional yellow dent corn) and ground corn particle size (600 or 900 m). From farrowing to weaning, there was a tendency for a corn source particle size interaction (P = 0.065) in sow body weight (BW) change. Sows fed 900 m Enogen Feed corn had decreased BW loss compared to sows fed other treatments, which were similar in weight loss. For sow average daily feed intake from farrowing to weaning, there was a corn source particle size interaction (P = 0.048) with sows fed 900 m conventional yellow dent corn having lower feed intake than the sows fed 600 m conventional yellow dent corn, whereas sows fed 900 m Enogen Feed corn had greater feed intake compared to the sows fed 600 m Enogen Feed corn. There was a tendency for a particle size main effect (P < 0.10) for litter average daily gain (ADG) and total litter gain, with sows fed corn ground to 600 m having increased litter ADG and total litter gain compared to sows fed corn ground to 900 m. In summary, there were few differences in sow or litter characteristics among those fed Enogen Feed corn or conventional yellow dent corn. Reducing particle size of both corn sources tended to increase litter ADG and weaning weights.